Lower limbs asymmetries in the agility and explosive strength in male football players - Albeanu, S.; Munteanu, R.; Calinescu Brabiescu, L.; Ghetu, R.; Burcea, B.; Fortan, C. (Baltic Journal of Health and Physical Activity, 2021)
Football game requires a permanent dynamic, in which players frequently perform changes of direction, with or without the ball. This requires explosive strength in the lower limbs as well as agility. The aim of the study was to measure the execution time within the changes of direction over different distances. A total of 20 male football players were selected (aged 17.6±1.27 years old), BMI 21.4 ± 1.99. For the explosive strength, two tests using Optojump (Microgate) were applied: CMJ and 5 jumps single leg left/right front/back drift. Each player also performed an agility test consisting of a single change of direction to the left and another one to the right, then a complete turn with three changes of direction, once to the left and once to the right. Regardless of the dominant part, in the simple agility test there were no significant differences between the left and right leg (p> 0.05), while in the multiple tests, these differences became significant, with a delay in execution on the left side (p<0.05). Also, a moderate correlation was found between explosive strength and agility (r=.544, p<.05). In the games of possession, positioning and rounds, they will be permanently changed in such a way as to use both legs for the symmetrical development of explosive strength. Technical elements with and without the ball will be introduced in all situations, such as: quick jump-departure with the ball at the foot and change of direction to the left and to the right. Players will play positioning roles opposite to the situation in which they normally work (left defenders will be used on the right side, etc.). In all cases, it is recommended to insist on avoiding additional movements that lead to a decrease in agility.